Eucharistia – hostina lásky v príprave na Baránkovu hostinu - Jurko, Jozef (Studia Pastoralne, 2020)
At the beginning of salvation, the first people live in the abundance of the Paradise, like at the feast of God’s goodness and love. That ended early, but since then people have celebrated every dining – food consummation – like a small feast connected to the Paradise. The biblical history refers to the phenomenon of eating food with someone as manifestation of friendship and favour. Jesus accepted invitations to feasts where unusual events unfolded and this escalated in the eating of the Last Supper. At this feast, he established the new and eternal covenant that would continue to be the feast of agapé, the feast of love. The apostles carried on doing it, as the Acts of the Apostles say, when they gathered to pray and break the bread. In the Church this is being done at every Mass, which is a feast in preparation for the eternal Feast of the Lamb in the Kingdom of God. A feast is at the beginning of human existence, in the biblical world, at the fullness of time when Jesus came, at every Mass and in the Apocalypse of St John as well. Every Eucharist is a remembrance, an update, but also a continuous feast, so we, being penetrated by Jesus,can take part in his eternal feast.